2005
DOI: 10.1038/sj.bjc.6602366
|View full text |Cite
|
Sign up to set email alerts
|

Expression of V1A and GRP receptors leads to cellular transformation and increased sensitivity to substance-P analogue-induced growth inhibition

Abstract: Small-cell lung cancer (SCLC) is a particularly aggressive cancer, which metastasises early. Despite initial sensitivity to radio-and chemo-therapy, it invariably relapses, so that the 2-year survival remains less than 5%. Neuropeptides particularly arginine vasopressin (AVP) and gastrin-releasing peptide (GRP) act as autocrine and paracrine growth factors and the expression of these and their receptors are a hallmark of the disease. ,N me Phe 8 ]-substance-P (6 -11) (SP-G) inhibit the growth of SCLC cells by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
2
16
0
2
Order By: Relevance
“…It is possible then, that the expression of genes encoding neuropeptides and their receptors is a process associated with cellular immortalization. Recently, it was demonstrated that expression of the human V1a receptor in CHO cells resulted in a transformed phenotype that was associated with a loss of contact inhibited growth [41]. In apparent agreement with this notion, it was shown that activation of PI3K is essential for the transformation of human mammary epithelial cells in culture [42].…”
Section: Discussionsupporting
confidence: 63%
“…It is possible then, that the expression of genes encoding neuropeptides and their receptors is a process associated with cellular immortalization. Recently, it was demonstrated that expression of the human V1a receptor in CHO cells resulted in a transformed phenotype that was associated with a loss of contact inhibited growth [41]. In apparent agreement with this notion, it was shown that activation of PI3K is essential for the transformation of human mammary epithelial cells in culture [42].…”
Section: Discussionsupporting
confidence: 63%
“…Expression of neuropeptides has been associated with neoplastic transformation (17), and there is evidence that lung CSC originates from neuroendocrine cells in the lung, which show an increased expression and response to neuropeptides (18)(19)(20)(21). We have shown that the development of chemoresistance to conventional chemotherapy in SCLC cells is accompanied by an increase in expression of neuropeptide receptors and subsequently increased sensitivity to broad-spectrum neuropeptide antagonists (22)(23)(24), suggesting that targeting neuropeptide receptors on SCLC cells may provide a new strategy to target chemoresistant disease.…”
Section: Introductionmentioning
confidence: 77%
“…The GLC14 and GLC16 cells were previously profiled by short tandem repeat profiling to confirm their origin from a single patient (25,26). GRP-R-and V 1A -Rexpressing CHO-K1 cells (23) were confirmed receptor positive by Western blot analysis. RPMI-1640, polyclonal rabbit antihuman AVP-R (V 1A ), was purchased from Chemicon International, rabbit anti-human GRP-R (Thermo Scientific), CD133/ 1-APC, CD133/2-PE, CD133/1, mouse IgG1-APC and mouse IgG1-PE (Miltenyi Biotec).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations